Efficacy of Procyanidins against In Vivo Cellular Oxidative Damage: A Systematic Review and Meta-Analysis. - Shugang Li; Mengchuan Xu; Qiang Niu; Shangzhi Xu; Yusong Ding; Yizhong Yan; Shuxia Guo; Feng Li (PLoS ONE)
Aims In this study, the efficacy of proanthocyanidins (PCs) against oxidative damage was systematically reviewed to facilitate their use in various applications. Methods A meta-analysis was performed by two researchers. Each investigator independently searched electronic databases, including Cochrane, PubMed, Springer, Web of Science, China National Knowledge Infrastructure (CKNI), China Science and Technology Journal Database (CSTJ), and WanFang Data, and analyzed published data from 29 studies on the effects of PCs against oxidative damage. Oxidative stress indexes included superoxide dismutase (SOD), malondialdehyde (MDA), catalase (CAT), glutathione (GSH), glutathione peroxidase (GPx), and total antioxidative capacity (T-AOC). Results Compared with the oxidative damage model group, PCs effectively improved the T-AOC, SOD, GSH, GPx, and CAT levels, and reduced the MDA levels; these differences were statistically significant (P < 0.05). In studies that used the gavage method, SOD (95% CI, 2.33-4.00) and GPx (95% CI, 2.10-4.05) were 3.16-fold and 3.08-fold higher in the PC group than in the control group, respectively. In studies that used the feeding method, SOD (95% CI, 0.32-1.74) and GPx (95% CI, -0.31 to 1.65) were 1.03-fold and 0.67-fold higher in the PC group than in the control group, respectively. Statistically significant differences in the effects of PCs (P < 0.00001) were observed between these two methods. MDA estimated from tissue samples (95% CI, -5.82 to -2.60) was 4.32-fold lower in the PC group than in the control group. In contrast, MDA estimated using serum samples (95% CI, -4.07 to -2.06) was 3.06-fold lower in the PC group than in the control group. The effect of PCs on MDA was significantly greater in tissue samples than in serum samples (P = 0.02). Conclusion PCs effectively antagonize oxidative damage and enhance antioxidant capacity. The antagonistic effect may be related to intervention time, intervention method, and the source from which the indexes are estimated.